Membangun Kesadaran Ekologis Melalui Nilai-Nilai Al-Qur'an dan Hadis: Studi Analisis Terhadap Buku Al-Qur'an Hadis Madrasah Aliyah Kelas XII BAB III - Ash Siddiqy, Hasbi; Solihin, Mohammad Muchlis (IAIN PONOROGO, 2025)
This article aims to analyze the ecological values contained in the Qur’an and Hadith, as presented in Chapter III of the Al-Qur’an Hadith textbook for Grade XII of the Madrasah Aliyah, and their implications for education and social awareness. Using a qualitative method based on content analysis and literature review, this study examines how theological concepts such as khalifah (stewardship), amanah (trust), ihsan (excellence in conduct), and the prohibition of fasād (destruction) are pedagogically framed in the textbook as the foundation of Islamic ecological ethics. The findings indicate that Chapter III incorporates a material structure that emphasizes the human–God–nature relationship (hablum minal ‘alam), yet there remains a gap between the depth of Qur’anic–Prophetic messages and their pedagogical implementation. Nevertheless, integrating ecological values into Qur’an–Hadith learning has been shown to enhance students’ environmental awareness by strengthening religious motivation, fostering environmentally friendly habits, and encouraging participation in school-based ecological activities. At the social level, Islamic ecological education facilitates the emergence of faith-based social movements, such as tree-planting initiatives, mosque-based waste banks, and plastic-reduction campaigns. This study affirms that the environmental values within Islamic teachings possess a strong transformative potential for developing ecological character and sustainable social ethics. Therefore, strengthening the integration of Islamic ecotheology within the madrasah curriculum constitutes a strategic step in cultivating environmental awareness among the younger generation.